MINUMAN INSTAN DARI EKSTRAK BUAH NANAS DAN EKSTRAK KULIT BUAH MANGGIS - Jumiati, Jumiati; Raswen, Efendi; Fitriani, Shanti (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2019)
Pineapple and mangosteen peel can be used as ingredients in making instant drinks. This research aims to get the best ratio of pineapple extract and mangosteen peel extract to instant drinks product, and measure the level of preference of panelists.Research method was Completely Randomized Designed which consisted of five treatments and each treatment was repeated three times. Treatments of pineapple and mangosteen were 100%, 90%, 10%, 80%, 20%, 70%, 30%, and 60%,40%. The data were statistically analyzed by the Duncan’s New Multiple Range Test (DNMRT) at 5% level. Results of analyzed showed that the ratio of pineapple extract and mangosteen extract significantly affected water content, ash content, pH, total sugar content, antioxidant activity, color, taste, and flavour. Based on this research, the best treatment was the product  consist of pineapple extract and mangosteen peel extract 90%; 10% which had moisture of 2,95%, ash content of 0,85%, pH of 5,86, total sugar content of 64,66%. Sensory assessment of instant drink by panelist showed that the drink had a yellow color, pineapple aroma. Keywords: Instant drink, pineapple extract, mangosteen feel extract.